Fluvial environmental disasters: risk perception and evaluation of government responses by riverine populations in Cacau Pirêra, Iranduba/AM: percepção de risco e avaliação de respostas governamentais por populações ribeirinhas em Cacau Pirêra, Iranduba/AM. - Guimarães, David Franklin da Silva; Belmiro, Camila dos Santos; Vasconcelos, Mônica Alves de; Pereira, Henriques dos Santos (Sustainability in Debate, 2019)
This article unveils the perceptions of vulnerable populations of the Amazon regarding the risks of river disasters and highlights their assessment of the effectiveness of government responses. The record of perceptions, assessments and identification of social vulnerabilities were obtained in interviews with focus groups formed by residents of Cacau Pirêra, in the Amazon. To characterize the environmental threats and vulnerabilities, fluviometric and altimetric data of the occupied areas were used. In that District, floods do not have to exceed normal limits to constitute environmental disasters and, in the perception of residents, pose more risks than ebb. Participants point to the low effectiveness of public policies as the main cause of the ineffectiveness of the government’s response to water disasters. Natural disaster studies should consider the interactions between the environmental and social aspects of territories to reach an understanding of the complexity of the context in which they occur.